Fixedness as a Criterion for the Idiomaticity of Nominal Compounds - Hu, Xiaoqin (Forum for Linguistic Studies, 2024)
Many studies have argued that idiomaticity judgment should be based on multiple aspects, including both semantic and formal fixedness, also known as inflexibility. However, the results delimiting idiomaticity are far from scarce. Although the validity of the notion of fixedness has been challenged, the fixedness of fixed expressions and collocations are still considered of the same nature, differing only in degree. The difference in fixedness between fixed expressions and collocations is still ambiguous, creating several barriers to further study of idiomaticity. This article aims to define the idiomaticity of nominal compounds by reviewing the fixedness of nominal compounds and that of collocations. The research was conducted on a finite lexical list based on French lexical resources. The parameters for fixedness were defined and annotated on the basis of the corpus provided in Sketch Engine, and the data were processed with the support of statistical models. The results reveal the difference in fixedness between nominal compounds and collocations, challenging the argument that collocations are constructions that stand on the continuum of free to fixed phrases. This study proposes a new perspective on fixedness and provides unique insight into the idiomaticity of nominal compounds.